1997
DOI: 10.1002/jor.1100150215
|View full text |Cite
|
Sign up to set email alerts
|

Similar effects of recombinant human insulin‐like growth factor‐I and II on cellular activities in flexor tendons of young rabbits: Experimental studies in vitro

Abstract: To improve the understanding of factors with the potential of affecting the healing of flexor tendons, this study compared the cellular effects of recombinant human insulin-like growth factor-II with those of recombinant human insulin-like growth factor-I in matched pairs of deep flexor tendons of young rabbits. Dose-response effects on the synthesis of DNA and matrix proteins of either factor alone or in combination were investigated in short-term culture, and effects on synthesis and turnover of matrix compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 29 publications
0
64
0
1
Order By: Relevance
“…The observation that local IGF1 expression is positively correlated with local collagen expression, and is also probably associated with the absolute synthesis of collagen, is supported by in vitro studies showing a dose-dependent effect of IGF1 on collagen synthesis in animal tendon explants (38)(39)(40). However, it has to be acknowledged that the limited number of in vivo studies in animals measuring the effect of GH supplementation on tendon/muscle collagen synthesis have yielded somewhat conflicting results (41,42).…”
Section: Collagen and Myofibrillar Proteinmentioning
confidence: 84%
“…The observation that local IGF1 expression is positively correlated with local collagen expression, and is also probably associated with the absolute synthesis of collagen, is supported by in vitro studies showing a dose-dependent effect of IGF1 on collagen synthesis in animal tendon explants (38)(39)(40). However, it has to be acknowledged that the limited number of in vivo studies in animals measuring the effect of GH supplementation on tendon/muscle collagen synthesis have yielded somewhat conflicting results (41,42).…”
Section: Collagen and Myofibrillar Proteinmentioning
confidence: 84%
“…Because several in vitro studies have shown a direct dose-response influence of many growth factors on cell migration, cell proliferation, and matrix synthesis (Abrahamsson, 1997;Thomopoulos, 2005;Costa et al, 2006;Haupt et al, 2006), it has been suggested that the local administration of increased concentrations of these growth factors through the use of PC could optimize the local healing environment and thus enhance the ability of biologically compromised tissues to generate a repair response (Marx, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1,[9][10][11][12] Recent in vitro studies using gene therapy approaches also hold promise for the treatment of tendon injury. [13][14][15] Growth factors that have been shown to influence cell metabolism in vitro 1,6 include insulin-like growth factor (IGF-I) [16][17][18][19][20] and fibroblast growth factor (b-FGF), 21,22 platelet-derived growth factor (PDGF) isoform B, 19,[21][22][23] and transforming growth factor-b (TGF-b). 20,24,25 Bone morphogenetic protein-12 (BMP-12) has been shown to stimulate cell proliferation and matrix synthesis.…”
Section: Introductionmentioning
confidence: 99%